Application of a recently proposed test to the hypernettedchain approximation for the electric double layer - Henderson, D.; Alawneh, M.; Saavedra-Barrera, R.; Lozada-Cassou, M. (Condensed Matter Physics, 2007)
Bhuiyan, Outhwaite, and Henderson, J. Electroanal. Chem., 2007, 607, 54, have studied the electric double
layer formed by a symmetric electrolyte in the restricted primitive model and suggested that an examination of
the product of the coion and counterion profiles, normalized to the one when the distance of an ion from the
electrode is large, is an interesting and useful test of a theory. This product is identically one in the Poisson-
Boltzmann theory but simulation results show that, at contact, this product can be greater or smaller than
one at small electrode charge but always seems to tend to zero at large electrode charge. In this study we
report the results of the hypernetted chain approximation (HNC/MSA version) for this product and find that, at
contact, for this theory this product is always greater than the one at small electrode charge but tends to zero
at large electrode charge. Бгуян, Аутбайт i Гендерсон (J. Electroanal. Chem., 2007, 607, 54), вивчаючи електричний подвiйний шар, сформований симетричним електролiтом в рамках спрощеної примiтивної моделi, показали, що дослiдження добутку нормованих на одиницю на великих вiдстанях профiлiв ко-iона i контр-iона є цiкавим та корисним тестом теорiї. Цей добуток є тотожно рiвним одиницi в теорiї Пуассона-Больцмана, але результати комп’ютерного моделювання показують, що на контактi цей добуток може бути бiльшим, або меншим вiд одиницi при малому зарядi на електродi, проте завжди прямує до нуля при великому зарядi на електродi. В роботi для згаданого добутку представлено результати гiперланцюжкового наближення (версiя HNC/MSA) i показано, що в цiй теорiї цей добуток є завжди бiльший за одиницю для малих величин заряду на електродi та прямує до нуля при великих значеннях заряду на електродi.